Analisis Kebijakan Hutang pada Subsektor Kontruksi dan Bangunan di Indonesia - Nurkomala Nurkomala; Yuliansyah Yuliansyah; yunia amelia (Jurnal Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: This article aims to find out how the independent variable affects the dependent variable. Asset growth, liquidity, and profitability are independent variables; debt policy is the dependent variable. Method: The types and sources of data in this study are quantitative research, with data sources through the Indonesian Stock Exchange web. The data used in this study is the ratio of asset growth, liquidity, and profitability, with the determination of the sample using the porposive sampling method and produces 51 samples of construction and building sub-sector companies. The reason for using the construction and building sub-sector is because the company is overshadowed by a higher debt burden since 2018 plus the Covid-19 pandemic. The analysis used in this study is multiple linear regression analysis using the software SPSS 26. Results: The result showed that indicate the asset growth and Profitability, liquidity, and variability all have a substantial negative impact for the policy of debt. Liquidity also has a significant positive impact on debt policy. Limitation: This research was only conducted at used only revolves around the building and construction that in 2018 until 2020, firms from the subsector should be registered on the Indonesia Stock Exchange Contributions: This exploration has contributed to the enrichment of aspects of the management accounting literature, especially in construction and building sub-sector companies.